PENGARUH ATTITUDE TOWARDS BEHAVIOUR, SUBJECTIVE NORMS, DAN PERCEIVED BEHAVIOURAL CONTROL TERHADAP INTENTION TO USE SHOPEE PAYLATER - Firman Maulana Adiyansyah (Publika Citra Media, 2026)
This study aims to analyze the influence of Attitude Toward the Behavior, Subjective Norms, and Perceived Behavioral Control on Intention To Use Shopee PayLater. Using a quantitative approach with purposive sampling method on 100 respondents of Shopee PayLater users from generation Z and millennials, data were analyzed using multiple linear regression. The results show that simultaneously the three variables have a significant influence of 47.4% on the intention to use Shopee PayLater. Partially, only Attitude Toward the Behavior has a positive and significant effect, while Subjective Norms and Perceived Behavioral Control have no significant effect. These findings indicate that users' positive attitudes are the main determinant in shaping the intention to use digital payment services, while social influence and perceived behavioral control have weaker roles in the context of using Shopee PayLater